Enhanced oxygen reduction activity of size-selected platinum subnanocluster catalysts: Ptn (n = 3–9). Issue 5 (26th January 2022) - Ohnuma, Akira; Takahashi, Koki; Tsunoyama, Hironori; Inoue, Tomoya; Zhao, Pei; Velloth, Archana; Ehara, Masahiro; Ichikuni, Nobuyuki; Tabuchi, Masao; Nakajima, Atsushi
Abstract : Pt n subnanoclusters ( n = 3–9) on a carbon substrate exhibit 1.6–2.2 times higher activity than the standard Pt/C catalysts. EXAFS experiments and DFT calculations show plausible structures and energetics for reaction intermediates in the processes. Abstract : Nanoclusters (NCs) are promising candidates to improve catalytic activity despite the controversial size specificity, because atomicity is a crucial parameter that determines the activity of platinum (Pt) NCs. This paper demonstrates the enhanced catalytic activity based on the charge redistribution in Pt sub-NCs containing three to nine Pt atoms (Pt n ; n = 3–9) on a glassy carbon substrate. The sub-NCs show 1.6–2.2 times higher activity than the standard Pt/C catalysts with a Pt crystallite diameter of 2 nm. The geometric structures are identified using rigorous structure analyses by X-ray absorption fine structure spectroscopy and density functional theory, and the activity origin within the supported Pt sub-NCs is theoretically discussed from viewpoints of energetics for reaction intermediates in the electrochemical processes. It should be possible to use sub-NCs in future fuel cell technologies as an active catalyst with a high atomic efficiency.